Kurikulum Ulumul Quran Bagi Santri di Pesantren Tahfidz - Ilyas Nasyirudin; Rizka Harfiani (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
Pesantren Baitul Quran Depok is one of the educational institutions that is concerned with the Quran, the curriculum is made not only learning tahfidz and tahsin alone, but also with understanding and practice in everyday life. The research method used is field research or field research which is a type of qualitative research. That is research that makes the research subject as the main instrument. at the boarding school. The results of the study that the ulumul Quran curriculum at the Baitul Quran Islamic boarding school in Depok are as follows: The purpose of learning ulumul Quran at the Baitul Quran boarding school in Depok is inseparable from the goals of Islamic education and the vision, mission of the Baitul Quran Foundation, which is to create a generation of Qurani, who are able to read and memorize and understand the contents of the Quran. Comprehensively, both in terms of text and context. the material taught uses the Mawarid al-bayan fi Ulum al-Quran book by Muhammad Afifuddin Dimyaty, namely; history of the Quranic ulum, Makki-madani, Sab'ah letters, qira'at, muhkam and mutasyabih, asbab an-nuzul, and ad-dakhil fi ulum Al-Quran, and mufassirun. Among the methods used are lecture, discussion, question and answer, recitation, and discovery methods. Evaluation of ulum Al-Quran learning at the Baitul Quran Islamic boarding school in Depok is divided into three categories, namely, daily evaluation, monthly evaluation and semester evaluation, while the evaluation of teachers is carried out by the head of education and caregivers as evaluators.